Time Management Strategies for Boarding School Students: The Role of Boarding School Programs and Support from Musrifah in Maintaining Academic and Organizational Balance - Azizah Bekti Pratiwi; Fitriah M. Suud (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Female students in an Islamic university dormitory balance their academic and organizational roles within an institutionally structured daily routine, in which dormitory advisors, known as musrifah, help shape how they manage that balance. This qualitative descriptive-interpretive study is based on semi-structured interviews with 16 participants (8 female students, 8 Musrifah) conducted between January 2026 and April 2026, and analyzed thematically across six phases. Three themes emerged. Time management functions as a negotiated priority within a scheduled institutional rhythm: female students delegate scheduling decisions to dormitory routines, thereby freeing up cognitive effort for the substance of academic tasks. The dormitory program functions as a disciplinary infrastructure, transforming imposed routines into internalized habits through the gradual and measured withdrawal of support by the musrifah. The relationship between the musrifah and the students forms a multi-layered, dual-role support system that combines formal supervision with residential guidance, providing emotional, informational, instrumental, and evaluative support from a single trusted source. These findings challenge individualistic assumptions in existing time management theory and expand the typology of social support by identifying a unique configuration of dual-role support. Residential institutions do more than enforce time management; they redistribute regulatory tasks through institutional rhythms, measured guidance, and formal support embedded within the domestic environment. These findings provide insights for the design of residential programs, the professional development of Musrifah, and the validity of individual-oriented time management measurement instruments